ANALISIS TINGKAT KEBERHASILAN MODEL CTL TERHADAP PEMAHAMAN KONSEP BAGIAN TUMBUHAN DI SEKOLAH DASAR - Alvin Alex Sander; Syofnidah Ifrianti; Yudesta Erfayliana (Universitas Islam Raden Rahmat Malang, 2026)
Abstract This study is a Systematic Literature Review (SLR) aimed at analyzing the effectiveness of the Contextual Teaching and Learning (CTL) model in improving elementary school students’ conceptual understanding of plant parts. Science instruction in elementary schools is often still theoretical and fails to connect the material to everyday life, resulting in low conceptual understanding among students. The CTL model was chosen because it is considered capable of bridging academic knowledge with students’ real-world contexts. The study employed a SLR approach following the PRISMA guidelines. Using the Publish or Perish (PoP) application on the Google Scholar and Crossref databases, the researcher successfully identified 999 articles. After undergoing a screening process, duplicate elimination, and evaluation based on inclusion and exclusion criteria, 15 SINTA-accredited scientific articles published between 2021 and 2025 were selected for further analysis. The synthesis results indicate that the consistent application of the CTL model effectively enhances students’ conceptual understanding of the structure and function of plant parts (roots, stems, leaves, flowers, fruits, and seeds). Students are more active and find the material easier to understand because learning is directly linked to everyday experiences. Key components of CTL, such as constructivism, inquiry, questioning, modeling, and authentic assessment, serve as supporting factors for success. This study concludes that CTL is an effective learning model for plant parts material in elementary schools, although there are still some implementation challenges, such as limited resources and teacher training.